2021
DOI: 10.1371/journal.pone.0246515
|View full text |Cite
|
Sign up to set email alerts
|

Assessing anxiety, depression and insomnia symptoms among Ebola survivors in Africa: A meta-analysis

Abstract: Background During health disaster events such as the current devastating havoc being inflicted on countries globally by the SARS-CoV-19 pandemic, mental health problems among survivors and frontline workers are likely concerns. However, during such health disaster events, stakeholders tend to give more precedence to the socio-economic and biomedical health consequences at the expense of mental health. Meanwhile, studies show that regardless of the kind of disaster/antecedent, all traumatic events trigger simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Insomnia symptoms frequently manifest in the face of acute life changes or stressors, such as pandemics, 69 and unsurprisingly, studies conducted during the COVID-19 pandemic have overwhelmingly and consistently shown a significant increase in insomnia symptoms, ranging from 18% to 63%. 16 , 37 , 70 , 71 Whilst some of these insomnia symptoms may be categorized as mild, it has been well accepted that transient sleep disturbances can later lead to chronic insomnia disorders.…”
Section: Pragmatic Focus On Sequelae Of Insomnia and Hypersomniamentioning
confidence: 99%
“…Insomnia symptoms frequently manifest in the face of acute life changes or stressors, such as pandemics, 69 and unsurprisingly, studies conducted during the COVID-19 pandemic have overwhelmingly and consistently shown a significant increase in insomnia symptoms, ranging from 18% to 63%. 16 , 37 , 70 , 71 Whilst some of these insomnia symptoms may be categorized as mild, it has been well accepted that transient sleep disturbances can later lead to chronic insomnia disorders.…”
Section: Pragmatic Focus On Sequelae Of Insomnia and Hypersomniamentioning
confidence: 99%
“…It is well-established that patients with eating disorders are already particularly well-characterized by eating-related concerns and are known to suffer from various psychological comorbidities [10]. It is important to note that patients with mental disorders struggled previously in the past during different pandemics such as Ebola [11]. Thus, the stress of the ongoing pandemic may potentially negatively impact these patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…13 Survivors of an Ebola epidemic in Africa reported feeling anxiety (14%), depression (15%), and insomnia (22%). 14 The sleep problems arising during the coronavirus disease (CO-VID-19) outbreak are severe and affect approximately 40% of people. 15 SARS-CoV-2 was first identified in December 2019 in Wuhan city, central China.…”
Section: Original Articlementioning
confidence: 99%
“…Each item is scored on a 5-point Likert scale from 0 to 4, yielding a total score of 0-28. The results were interpreted as follows: absence of insomnia (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). Numerous studies have proven that the ISI is a valid and reliable instrument.…”
Section: Study Questionnairementioning
confidence: 99%